Did the German aviation tax have a lasting effect on passenger numbers? - Viola Helmers; Edwin Van der Werf (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
The taxation of aviation is a frequently discussed component of governments' efforts to mitigate greenhouse gas emissions. This study examines the impact of the German aviation tax on passenger numbers during the period 2011-2019 using five panel data estimators and a Specification Curve Analysis (SCA) to assess the robustness of the results to changes in the specifications of the econometric model. Employing five base models, we find that the tax induced a 6-11% reduction in the number of passengers departing annually from Germany in the first two years after implementation. For later years, estimated effects are more ambiguous. The SCA, comprising 175 alternative specifications, corroborates our main findings while showing a slightly wider range of effect sizes, especially on the upper bound. The results show that the choice of econometric method can affect research outcomes, especially for the fourth year of the tax and onward. – – Die Besteuerung des Luftverkehrs ist eine häufig diskutierte Maßnahme von Regierungen zur Verringerung von Treibhausgasemissionen. Diese Studie untersucht die Auswirkungen der deutschen Luftverkehrsteuer auf Passagierzahlen im Zeitraum 2011-2019 mit Hilfe von fünf Paneldatenschätzern und einer Specification Curve Analysis (SCA), um die Robustheit der Ergebnisse gegenüber Änderungen in den Spezifikationen des ökonometrischen Modells zu bewerten. Unter Verwendung von fünf verschiedenen Schätzern stellen wir fest, dass die Steuer in den ersten beiden Jahren nach Einführung der Steuer zu einem Rückgang der Anzahl der jährlich aus Deutschland abfliegenden Passagiere um 6-11 % führte. Für die nachfolgenden Jahre sind die geschätzten Effekte uneindeutig. Die SCA, welche weitere 175 alternative Spezifikationen umfasst, bestätigt unsere Hauptergebnisse und zeigt eine etwas breitere Spanne von Effektgrößen, insbesondere im oberen Bereich. Unsere Ergebnisse zeigen, dass die Wahl der ökonometrischen Methode die Ergebnisse maßgeblich beeinflussen kann, in diesem Fall insbesondere für die Effekte ab dem vierten Jahr der Steuer.
Keywords: C21; C23; H23; R48; 330; Aviation policy; aviation tax; passenger tax; transport economics; dynamic panel model; specification curve analysis